Edukasi Kesehatan: Perawatan Kaki terhadap Pengetahuan, Sikap dan Tindakan Pencegahan Ulkus Kaki Diabetik - Munali Munali; Kusnanto Kusnanto; Hanik Endang Nihayati; Hidayat Arifin; Rifky Octavia Pradipta (Critical Medical and Surgical Nursing Journal (CMSNJ), 2019)
Introduction: People with diabetes mellitus were at 15% risk of developing diabetic foot ulcers. Diabetic foot ulcers can be prevented if people with DM have the knowledge, positive attitude and thus able to perform the diabetic foot care. The aim was to determine the effect of health education on knowledge, attitudes and preventionof diabetic foot ulcers of people with diabetes mellitus. Method: quasi-experiment research design pretest-posttest control group design. Sample was DM patients who visited the Bangkalan City Health Center, recruited by purposive sampling technique with sample size of 35 people in the treatment group and 35 people in the control group. Independent variable was the health education and the dependent variables were knowledge, attitudes and of diabetic foot ulcers. Data were collected with questionnaires andthen analyzed by Wilcoxon Sign Rank Test and Mann-Whitney Test.Result: The results showed that there was an effect of health education on knowledge (p=0.000), attitudes (p=0.000) and preventive actions (p=0.000) of diabetic foot ulcers.Conclussion: Health education was important as an effort to persuade DM patients to take charge on their knowledge and attitude foot care by firstly enhancing.